Development and storage stability of conjugated linoleic acid fortified yogurt - NAEEM,Sadia (2022)
Abstract The core objective of this research work was to fortify milk with conjugated linoleic acid (CLA) and to develop yogurt. Cow milk was analyzed for proximate analysis, minerals content, fatty acid profile and CLA content. After chemical analysis, milk was fortified with 1, 2 and 3% of CLA and yogurts were made. CLA fortified yogurts of cow milk was analyzed for proximate analysis, titratable acidity, synersis, pH, viscosity, CLA and sensory evaluation. Results showed that the proximate composition significantly changed particular fat. CLA contents also changed significantly. The value of titratable acidity was changed significantly in all treatments whereas the entire samples showed lower value of pH after 14 days storage. All treatments showed higher values of viscosity at 0 day and decreased significantly at 14th day. Yogurt samples showed the lowest syneresis value after 14 days of storage. All the treatments were showed overall acceptability. The sensory evaluation indicated good sensory and high textural quality with the maximum consumer satisfactoriness. The results showed that CLA fortification can meet recommended CLA dietary intake for health benefits.